The Effects of MISUKE For Underweight Children - Asmarudin Pakhri; Siti Nur Rochimiwati; Adriyani Adam; Hikmawati Mas’ud (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background : Malnutrition problems such as underweight was unhealthy (pathological) conditionsthat arise from not enough eating or consuming less energy and protein for a certain period of time.The results of monitoring the nutritional status of toddlers (0-59 months) in 2018 from Basic HealthResearch with WAZ Index, 17,6% children in underweight status. MISUKE (vegetable oil, milk &soybean) is a nutrient-dense supplement made from vegetable oil, skim milk and soybeans which are ahigh source of energy and protein but in small volume and in powder form.Objective : The aims of this study was to determine the effect of MISUKE formula on the nutritionalstatus of underweight children.Methods : This research design was quasi-experimental research with pretest and posttest approaches.Samples taken by 30 underweight children under five. This research was carried out in working area ofSudiang Raya Health Center in Makassar city.Results : The results showed that there was an increase in body weight before and after consumeMISUKE around 0.25 grams with a p value of 0,000, besides that there was a significant increase inenergy and carbohydrate intake after giving misuke with p values respectively (0,000 and 0.001), andfor There was also an increase in fat protein intake, but not significantly with p values (0.56) and (0.51),respectively. Thus, MISUKE can be used as an alternative food for malnourished children.Conclusion : MISUKE formulation used consists of 12 grams of vegetable oil, 6 grams of skimmedmilk, 12 grams of soy bean flour, 4 grams of granulated sugar. The nutritional value of MISUKE is190.8 kcal energy, 6.5 grams of protein, 14.5 grams of fat, and 10.7 grams of carbohydrates, while thechange in nutritional status for weight before ranging from 10.48 grams and the increase of 0.25 gramsafter MISUKE treatment with an average body weight range of 10.73.